(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The present search aims to investigate the opinions of the schools directors about the role of Dialogic and News programs in Citizenship education on the Syrian channels in the following directions: ( Affiliation The Rights The Duties Value and Puplic Participation) in the light of the Syrian crisis since 2011. And that was happened by investigating the opinions of a sample consisted of( 25) singles of the directors of the second –episode schools in Lattakia city. To achieve the purpose of the search a questionnaire has been created and distributed on a study sample. By depending on the suitable statistic ways it was reached to the following results: 1.The dialogic and news programs on the Syrian channels are educating citizenshipin the light of the crisis in a medium degree according to the opinions of the directors of the second- episode schools in Lattakia city. 2.The dialogic and news programs are strengthening the national affiliation in a great degree according to the members of the sample. 3.The lack of difference among the middle- level answers of the members of the sample returns of the : genderscientific methodundergo training courses variable